Health and economic impact associated with rheumatoid arthritis discharges: a cost analysis of a two-year cohort in Mexico - Carlos Fernando Mendoza-Gutierrez; Diana Montiel-Ojeda; Delfino Vargas-Chanes; Nelly Cisneros-González; José Esteban Fernández-Gárate; Blanca Godina-Ortiz; Patricia Clark (BMC, 2023)
Abstract Background Rheumatoid arthritis is a highly prevalent disease. Patients undergo various medical and pharmacological treatments, which have an economic impact on hospitals. The aim of this study was to estimate the direct economic costs of Mexican Social Security Institute (IMSS) resources used to provide healthcare to adult patients with rheumatoid arthritis in 2016-2017. Methods Data of patients aged > 18 years with Rheumatoid Arthritis (RA) were obtained from databases and public information sources to estimate the use of IMSS resources for the target population. Total costs were estimated by means of the macro-costing method, employing the diagnosis-related group (DRG). Each DRG of the IMSS was constructed with one of the diagnoses and the respective combination of clinical characteristics included in the ICD-9. This study was conducted from the national perspective of IMSS, the largest healthcare service administrator in the country. As such, it can be considered representative of the broader healthcare landscape in Mexico. Results The total cost per year of furnishing inpatient care to RA patients was found to be $170,099,794 MXN ($9,096,245.67 USD) for 2016 and $167,039,481 MXN ($8,932,592.57 USD) for 2017, implying an enormous economic impact on the government budget for Mexican public health services. Conclusions Our results demonstrate that the direct costs of musculoskeletal and cardiovascular surgery represented the highest costs of RA in-hospital care at IMSS (the largest health institution in Mexico) in 2016 and 2017. Further studies are needed that include the cost of drugs and other indirect costs in addition to our results to get the most accurate approximation of the cost of living with RA.